The Caenorhabditis elegans iodotyrosine deiodinase ortholog SUP-18 functions through a conserved channel SC-box to regulate the muscle two-pore domain potassium channel SUP-9. - Ignacio Perez de la Cruz; Long Ma; H Robert Horvitz (PLoS Genetics)
Loss-of-function mutations in the Caenorhabditis elegans gene sup-18 suppress the defects in muscle contraction conferred by a gain-of-function mutation in SUP-10, a presumptive regulatory subunit of the SUP-9 two-pore domain K(+) channel associated with muscle membranes. We cloned sup-18 and found that it encodes the C. elegans ortholog of mammalian iodotyrosine deiodinase (IYD), an NADH oxidase/flavin reductase that functions in iodine recycling and is important for the biosynthesis of thyroid hormones that regulate metabolism. The FMN-binding site of mammalian IYD is conserved in SUP-18, which appears to require catalytic activity to function. Genetic analyses suggest that SUP-10 can function with SUP-18 to activate SUP-9 through a pathway that is independent of the presumptive SUP-9 regulatory subunit UNC-93. We identified a novel evolutionarily conserved serine-cysteine-rich region in the C-terminal cytoplasmic domain of SUP-9 required for its specific activation by SUP-10 and SUP-18 but not by UNC-93. Since two-pore domain K(+) channels regulate the resting membrane potentials of numerous cell types, we suggest that the SUP-18 IYD regulates the activity of the SUP-9 channel using NADH as a coenzyme and thus couples the metabolic state of muscle cells to muscle membrane excitability.